2021
DOI: 10.3390/genes12081195
|View full text |Cite
|
Sign up to set email alerts
|

Rhythmic Regulation of DNA Methylation Factors and Core-Clock Genes in Brain Structures Activated by Cocaine or Sucrose: Potential Role of Chromatin Remodeling

Abstract: The circadian system interacts with the mesocorticolimbic reward system to modulate reward and memory in a time-of-day dependent manner. The circadian discrimination of reward, however, remains difficult to address between natural reinforcers and drugs of abuse. Circadian rhythms control cocaine sensitization and conversely cocaine causes long-term alteration in circadian periodicity in part through the serotonergic neurotransmission. Since neural circuits activated by cocaine and natural reinforcers do not co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 105 publications
(157 reference statements)
0
5
0
Order By: Relevance
“…A global DNA methylation analysis showed an increase in 5-mC by cocaine, consistent with repression of critical core-clock genes by cocaine. The DNA methylation state of some core-clock genes (clock, cry2) was consistent with an increase in global DNA methylation in response to cocaine (submitted article In a recent study, we found that cocaine and sucrose differentially regulate genes involved in DNA methylation and circadian gene expression in certain rat brain structures (PFC, CPu) (submitted article [203]). A global DNA methylation analysis showed an increase in 5-mC by cocaine, consistent with repression of critical core-clock genes by cocaine.…”
Section: Epigenetic Connection Between Circadian Rhythms and Addictionmentioning
confidence: 56%
See 4 more Smart Citations
“…A global DNA methylation analysis showed an increase in 5-mC by cocaine, consistent with repression of critical core-clock genes by cocaine. The DNA methylation state of some core-clock genes (clock, cry2) was consistent with an increase in global DNA methylation in response to cocaine (submitted article In a recent study, we found that cocaine and sucrose differentially regulate genes involved in DNA methylation and circadian gene expression in certain rat brain structures (PFC, CPu) (submitted article [203]). A global DNA methylation analysis showed an increase in 5-mC by cocaine, consistent with repression of critical core-clock genes by cocaine.…”
Section: Epigenetic Connection Between Circadian Rhythms and Addictionmentioning
confidence: 56%
“…A global DNA methylation analysis showed an increase in 5-mC by cocaine, consistent with repression of critical core-clock genes by cocaine. The DNA methylation state of some core-clock genes (clock, cry2) was consistent with an increase in global DNA methylation in response to cocaine (submitted article [203]). Yet, additional gene-specific DNA methylation experiments are required to ascertain a definite link between the circadian timing system and its contribution to addiction.…”
Section: Epigenetic Connection Between Circadian Rhythms and Addictionmentioning
confidence: 63%
See 3 more Smart Citations